MPR, TRANSISI KEDAULATAN RAKYAT DAN DAMPAK POLITIKNYA - Prayudi Prayudi (Sekretariat Jenderal DPR RI, 2012)
Four times amendments of the 1945 Constitution has resulted in an MPR which is longer as the highest state institution, but as a common high state institution equal with others. This change has been made based on the argument that power sovereignty is upheld by the people and shall be performed in accordance with the amended 1945 State Constitution. This political situation a process of transition of power sovereignty since MPR members are not again appointed representatives but elected representatives, who are chosen in general elections. This transition causes the changes of MPR tasks, duties, and authorities as a high state institution.